Enhancing Energy Efficiency of Cumene Production Through Reactor Output Recycling Modification in a Heat Exchanger - Sutjahjo, Finishia; Medri, Lathifa; Alyani, Syarafina; Budhy, Cindy Leviona (Journal of Chemical Engineering Research Progress, 2024)
Cumene production generally involves irreversible and exothermic reactions that leads to an increase in product temperature and needs to be cooled for further processes. The high temperature of reactor product can be utilized as a heat transfer fluid in heat exchanger. This modification process is essential for improving energy efficiency by recycling the reactor output with high temperature as a heat transfer fluid, so that the implementation of replacing the heater with a heat exchanger can be carried out for the process of increasing the initial feed temperature. In an effort to enhance energy efficiency in the cumene production process, simulations were conducted using HYSYS and the comparison of energy efficiency for both basic and modified processes can be evidenced by comparing the total amount of energy required during the process. The results shows that the total amount of energy required for the modified process is 39,814,003.7 kJ/h, while for the basic process is 40,588,937.4 kJ/h, with a difference of 774,933.7299 kJ/h. Since the total amount of energy required in the modified process is smaller than the basic process, then the modification process will increase the energy efficiency of cumene production. Copyright © 2024 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).